Application of the Quality of Research for Development Framework to Initiative Reviews: Lessons Learned - CGIAR Independent Science for Development Council (CGIAR Independent Science for Development Council, 2022)
To improve future ISDC external review of CGIAR proposals, ISDC conducted an ex-post analysis of the Initiative review process through a reviewer survey, CGIAR stakeholder consultations, examination of QoR4D reviewer scoring divergence, and Initiative Design Team (IDT) responses to ISDC reviews. The Lessons Learned report details the analysis' recommendations grouped by: (1) QoR4D and its application to Initiatives, (2) insights for the design of the Initiative proposal template, and (3) areas for deeper consideration by IDTs and senior leadership in developing future proposals.